Are ultrasound foetal circumference measurement methods interchangeable?. (August 2019) - John Dudley, Nicholas
A variety of methods is available for the ultrasound measurement of foetal circumferences; ellipse fitting and derived measurements are often used interchangeably based on an assumption of equivalence, despite evidence that results may differ. The aim of this study was to investigate the differences between ellipse fitting and derived circumferences in clinical practice. Head and abdominal circumferences originally measured using ellipse fitting were retrospectively derived from anterior–posterior and transverse diameters using a widely used formula. Where the necessary measurements were available, foetal weight was estimated. Differences between ellipse fitted and derived measurements were compared using Bland–Altman plots. Images from 65 patients (gestational age 20 to 40 weeks) were collected; four head circumference and five abdominal circumference images were excluded due to poor image quality. Data were available for estimated foetal weight calculation for 48 patients. There were small systematic differences between ellipse fitted and derived measurements. Random differences varied between 20 week scans, early growth scans and later growth scans, so were analysed in these three groups. The 95% confidence intervals were ±6 mm (±3%), ±7 mm (±2%) and ±20 mm (±6%) for head circumference at 20 weeks, earlier growth scans and later scans, respectively; the 95% confidence intervals for abdominal circumference were ±7 mm (±5%), ±11 mm (±5%) and ±17 mm (±6%) and for estimated foetal weight were ±23 g (±6%), ±69 g (±5%) and ±311 g (±12%). Foetal circumference measurement methods are not interchangeable. The derived method should be used where size, growth and estimated foetal weight charts are based on this method.